Membrane-Associated α-Tubulin Is Less Acetylated in Postmortem Prefrontal Cortex from Depressed Subjects Relative to Controls: Cytoskeletal Dynamics, HDAC6, and Depression - Singh, Harinder; Chmura, Justyna; Bhaumik, Runa; Pandey, Ghanshyam N.; Rasenick, Mark M. (The Journal of neuroscience, 2020)
Cytoskeletal proteins and post-translational modifications play a role in mood disorders. Post-translational modifications of tubulin also alter microtubule dynamics. Furthermore, tubulin interacts closely with Gα s , the G-protein responsible for activation of adenylyl cyclase. Postmortem tissue derived from depressed suicide brain showed increased Gα s in lipid-raft domains compared with normal subjects. Gα s , when ensconced in lipid rafts, couples less effectively with adenylyl cyclase to produce cAMP, and this is reversed by antidepressant treatment. A recent in vitro study demonstrated that tubulin anchors Gα s to lipid rafts and that increased tubulin acetylation (due to HDAC6 inhibition) and antidepressant treatment decreased the proportion of Gα s complexed with tubulin. This suggested that deacetylated-tubulin might be more prevalent in depression. This study examined tubulin acetylation in whole-tissue homogenate, plasma membrane, and lipid-raft membrane domains in tissue from normal control subjects, depressed suicides, and depressed nonsuicides (human males/females). While tissue homogenate showed no changes in tubulin acetylation between control, depressed suicides, and depressed nonsuicides, plasma membrane-associated tubulin showed significant decreases in acetylation from depressed suicides and depressed nonsuicides compared with controls. No change was seen in expression of the enzymes responsible for tubulin acetylation or deacetylation. These data suggest that, during depression, membrane-localized tubulin maintains a lower acetylation state, permitting increased sequestration of Gα s in lipid-raft domains, where it is less likely to couple to adenylyl cyclase for cAMP production. Thus, membrane tubulin may play a role in mood disorders, which could be exploited for diagnosis and treatment. SIGNIFICANCE STATEMENT There is little understanding about the molecular mechanisms involved in the development of depression and, in severe cases, suicide. Evidence for the role of microtubule modifications in progression of depressive disorders is emerging. These postmortem data provide strong evidence for membrane tubulin modification leading to reduced efficacy of the G protein, Gα s , in depression. This study reveals a direct link between decreased tubulin acetylation in human depression and the increased localization of Gα s in lipid-raft domains responsible for attenuated cAMP signaling. The evidence presented here suggest a novel diagnostic and therapeutic locus for depression.